Analisis Kebutuhan Media Informasi Tempat Wisata Ramah Hewan Peliharaan di Kota Bandung - Ivenabaat Nurzahra; Mulki Tawakal Rosady; Rosa Karnita (Indonesian Journal of Tourism and Leisure, 2022)
This study aims to analyze the needs of pet owners in obtaining information about pet-friendly tourist attractions in Bandung. The city, called the Paris van Java, has many pet-friendly attractions. However, information media which contains data for pet owners who want to bring their pets along for recreation to pet-friendly tourist spots in Bandung, has yet to be found. Then an analysis of the needs of pet owners was carried out using qualitative research methods. Data were collected through questionnaires, observation and internet searching. All data that has been collected is then analyzed using thematic analysis. The analysis resulted in the identification of pet-friendly tourist attractions in detail, which is needed by tourists who have pets. Some of them are the types of places, rules, policies, social environment, and facilities of pet-friendly tourist spots to be considered before bringing pets to the intended location. Pet owners will be helped by creative forms of information, such as mobile applications that contain all complete information according to the needs of pet owners. Other information media, such as information boards or signage installed at tourist sites, can also help direct visitors who bring their pets.